Simulation of tensile behavior of frp composite material using finite element analysis - Tan, Jun Kang (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Fiber reinforcement polymer (FRP) composites material possesses excellent properties such as high specific stiffness, high strength-to-weight ratio, resistance of corrosion and weariness. However, number of factors control like type, orientation and architecture of fiber will be effecting the mechanical properties of FRP composite, thus, a study to compare the number of factor controls using tensile test through finite element analysis (FEA) and experimental method are essential.